Sistem Pendukung Keputusan Pemilihan Volunteer Terbaik Dengan Metode AHP Dan TOPSIS Pada Gereja GBI Glow Fellowship Centre Medan - Restu Berkat Juang Waruwu (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2021)
In the GBI Glow Fellowship Center Medan church every year it holds a selection of the best volunteers from several other volunteers to be given awards or say thank you for the church service for 1 year which is considered to have better performance than other volunteers. This is done as a reference to motivate other volunteers to be more serious in providing services. In selecting the best volunteers, they often experience problems, namely lack of transparency, are still commercial or traditional so that the results are not as expected and have not been systemized in inputting all the data that will organize voluntary monthly performance data, lack of infrastructure tools such as insufficient computers, data control tools and many other things. For the selection of the best volunteers, a selection of volunteer candidates is carried out with the specified criteria, so that there are no errors in the selection, a decision system is needed using the Analytical Hierarchy Process and Technique for Order Preference by Similarity to Ideal Solution method. By designing this decision support system, it can help the GBI Glow Fellowship Center Medan Church in selecting the best volunteers.